OPTIMASI PENGIRIMAN USAHA ISI ULANG AIR MINUM ARISTA WATER RO - Rahmat Fauzan; Putra Bagus Nugroho, Paduloh (Jurnal Kesehatan, 2024)
The importance of MSMEs in a country's economy and the key to their business success is the key to production costs. Drinking water depot is an industrial business that converts swamp water into drinking water and sells it directly to buyers, but problems are often found in distribution to customers. The purpose of this study is to determine the optimal distribution cost. The Stepping Stone method seems effective to solve this problem, the first and second solutions have the same cost even though the delivery is done by different drivers. The profit that can be obtained by the first sender gets a fee of Rp. 52,500 for 35 gallons a day and the profit by the second sender is Rp. 37,500 for 25 gallons a day.